Calling #TimesUp on the TV period drama rape narrative. (September 2019) - Byrne, Katherine; Taddeo, Julie Anne
This article explores the rape plotlines in Poldark (2015–), Outlander (2014–) and Banished (2015), which mostly take place prior to #MeToo and offer a pre-watershed insight into a time when rape could still be romanticised and eroticised in a way which might not, or at least should not, be possible after October 2017. However, these plots opened up conversations about consent, rape myths and rape fantasy and hence form part of the dialogue and increasingly public awareness about sexual violence which made #MeToo possible in the first place. How fans respond to rape narratives pre- and post-#MeToo is also considered.